Ethnocompetitiveness, relations, and networks: towards rural sustainability. Issue 7 (3rd October 2017) - Lugo-Morin, Diosey Ramón
ABSTRACT: Small producers face various obstacles in placing their products on the global market. The most important obstacle is associated with the generation of innovative products in a dynamic context. This article presents a case study which provides support for a methodology designed to quantify the competitiveness of small and medium-sized local producers in relation to other producers in the same region and nation. It explores how the evolution of knowledge relates to the ability of agricultural producers to sell their products in regional and international markets. To do so, it utilises the concept of ethnocompetitiveness, which can be understood as the hybridisation of local knowledges with external or codified knowledge.